Święty Walenty we frazeologizmach i przysłowiach polskich - Buława, Monika (Słowiańska frazeologia gwarowa II, 2020)
VALENTINE IN POLISH PHRASEMES AND PROVERBSThere are references to St. Valentine in Polish phraseology and paremiology in which he has two functions: as a guardian of epileptics whose name used to be included in old names of epilepsy and as a patron of February 14. In the first case there was a specific reversal of the role of a saint as his name started to appear in phrasemes to denote the devil. This kind of transformations can be encountered in the seventeenth century picaresque literature. In Kashubian dialects the adjective formed from the name of the saint could be found in swearwords and expletives to define the noun devil or independently (as a result of substantivisation). It has been proved that calendar proverbs, including the forecasting ones that refer to St. Valentine’s day, exist both in sources that represent General Polish as well as collections of folk proverbs.